Development of an enthalpy‐based frozen soil model and its validation in a cold region in China. Issue 10 (19th May 2016) - Bao, Huiyi; Koike, Toshio; Yang, Kun; Wang, Lei; Shrestha, Maheswor; Lawford, Peter
Abstract: An enthalpy‐based frozen soil model was developed for the simulation of water and energy transfer in cold regions. To simulate the soil freezing/thawing processes stably and efficiently, a three‐step algorithm was applied to solve the nonlinear governing equations: (1) a thermal diffusion equation was implemented to simulate the heat conduction between soil layers; (2) a freezing/thawing scheme used a critical temperature criterion to judge the phase status and introduced enthalpy and total water mass into freezing depression equation to represent ice formation/melt and corresponding latent heat release/absorption; and (3) a water flow scheme was employed to describe the liquid movement within frozen soil. In addition, a parameterization set of hydraulic and thermal properties was updated by considering the frozen soil effect. The performance of the frozen soil model was validated at point scale in a typical mountainous permafrost basin of China. An ice profile initialization method is proposed for permafrost modeling. Results show that the model can achieve a convergent solution at a time step of hourly and a surface layer thickness of centimeters that are typically used in current land surface models. The simulated profiles of soil temperature, liquid water content, ice content and thawing front depth are in good agreement with the observations and the characteristics of permafrost. The model is capable of continuously reproducing the diurnal and seasonal freeze‐thaw cycle and simulating frozen soil hydrological processes. Key Points: An enthalpy‐based frozen soil model was developed to simulate freezing/thawing processes efficiently The frozen soil model was validated against soil observations from a permafrost station The model simulation is in good agreement with the observed soil freezing/thawing characteristics